IMPROVING STUDENTS SPEAKING ABILITY BY USING ROLE-PLAY(A CLASSROOM ACTION RESEARCH AT THE SIXTH GRADE OF SDN 01 KARANGTURI-LASEM) - SALAM, AFDHALUS (2011)
This research paper is aimed at describing the implementation of role play technique on teaching speaking to the sixth grade student at elementary school of SD N 01 Karangturi-Lasem (classroom action research), to describe the effectiveness using role play technique on teaching speaking to the sixth grade student at elementary school of SD N 01 Karangturi-Lasem (classroom action research), to describe the strength and the weakness of the role play technique on teaching speaking to the sixth grade student at elementary school of SD N 01 Karangturi-Lasem (classroom action research). This study is a descriptive qualitative research. The data in this research are derived from event, document and informant. The data are gained from observation and interview with the teacher and the students. Based on the observation and interview, the writer draws some conclusion about: 1) the implementation of role play, it is proved by the students response shown in speaking, the students become more active, they help each other in doing exercises, sharing their knowledge by speaking ability by using role-play, playing characteristic well and solving the problem first before consult to the teacher, 2) the effectiveness using role play technique on teaching speaking, it can be known that the result of the students in perform, working in pairs and evaluating the other students are grow from the first observation till the last observation. It is proved by the increasing number of the students in doing the indicator each cycle which had been done by the researcher and the teacher. The average of the pre-test is 40, 93 there were 4 of the students in fair, 9 of the students in poor and 1 of the students in failed, the average of the cycle one is 48,36 there were 1 of the students in good, 9 of the students in fair and 1 of the students in poor, the average of the cycle two is 58,28, there were 6 of the students in fair and 8 of the students in poor level and the last, the average of the post-test is 62,14, there were 9 of the students in fair and 5 of the students in poor level.